2014
DOI: 10.1016/j.jas.2013.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Isotope evidence for the use of marine resources in the Eastern Iberian Mesolithic

Abstract: a b s t r a c tThere are relatively few coastal Mesolithic sites in the Iberian Mediterranean region, probably due to a number of factors including sea level changes and the disappearance of sites due to agriculture and urbanisation. However, recent excavations have uncovered inland sites that have marine faunal remains (i.e. molluscs and fish) and lithics from the coastal area, which both indicate interactions between the coast and the upland valleys. These inland sites are located at a distance of 30e50 km f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
(47 reference statements)
1
54
0
1
Order By: Relevance
“…Stable carbon isotopic compositions are also indices of marine food consumption because the source of carbon used by plants differs in oceanic and terrestrial ecosystems, causing the tissue δ 13 C of marine mammals and fish to be~8‰ higher than those of terrestrial animals (Chisholm et al 1982). Brackish and estuarine fish, by contrast, typically have lower δ 13 C than marine fish (Salazar-García et al, 2014b). Krueger and Sullivan (1984) have shown that dietary protein is the primary influence on the carbon-isotope composition of collagen (δ 13 C col ) and thus does not provide clear insights into the isotopic composition of the remaining macronutrients (i.e., lipids and carbohydrates).…”
Section: Isotopic Backgroundmentioning
confidence: 99%
“…Stable carbon isotopic compositions are also indices of marine food consumption because the source of carbon used by plants differs in oceanic and terrestrial ecosystems, causing the tissue δ 13 C of marine mammals and fish to be~8‰ higher than those of terrestrial animals (Chisholm et al 1982). Brackish and estuarine fish, by contrast, typically have lower δ 13 C than marine fish (Salazar-García et al, 2014b). Krueger and Sullivan (1984) have shown that dietary protein is the primary influence on the carbon-isotope composition of collagen (δ 13 C col ) and thus does not provide clear insights into the isotopic composition of the remaining macronutrients (i.e., lipids and carbohydrates).…”
Section: Isotopic Backgroundmentioning
confidence: 99%
“…Lubell et al 1994;Schoeninger and DeNiro 1984) and also help to detect freshwater and estuarine fish consumption (e.g. Lillie et al 2011;Richards et al 2015;Salazar-García et al 2014). Moreover, δ 13 C can discriminate the intake of plants with different photosynthetic pathways and the animals that consumed them (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The application of these analytical techniques in Mediterranean Iberia has significantly increased during the past few years, creating an important corpus of dietary data from the region. Studies from the Palaeolithic (García-Guixé et al, 2009;Salazar-García et al, 2013a), Mesolithic (Fernández-López de Pablo et al, 2013;García-Guixé et al, 2006;Salazar-García et al, 2014a), Neolithic-Chalcolithic (Fontanals-Coll et al, 2015;Fuller et al, 2010;García-Borja et al, 2013;McClure et al, 2011;De Juan, 2004, 2007;Salazar-García, 2009, 2011a, 2014, Bronze Age (McClure et al, 2011;Polo-Cerdá et al, 2007;Romero and De Juan, 2007), Iron Age (Salazar-García et al, 2010), Punic Salazar-García, 2011b), Roman and Medieval (Alexander et al, 2015;Fuller et al, 2010;Salazar-García et al, 2014b) periods have been performed in Mediterranean Iberia and the nearby island of Ibiza. However, to date only a few studies have had a wide diachronic approach to diet in Spain (see Fuller et al, 2010;Salazar-García et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%